Production of calcium carbonate with different morphology by simultaneous CO2 capture and mineralisation. Issue 41 (October 2020) - Marin Rivera, Rodolfo; Van Gerven, Tom
Highlights: Ca conversion was below 15 wt.% in the absence of alkaline reagents. Ca conversion was above 80 wt.% with CO2 -absorption and mineral carbonation. Vaterite and aragonite particles were produced at 30 °C. Pure aragonite prevailed at 70 °C. Mg concentration of 0.06 g/L did not affect the formation of pure aragonite. Abstract: In this work, the precipitation of high-quality calcium carbonate (PCC) from synthetic Ca-rich solutions was investigated. A mixture of Ca and Mg salts were considered to reproduce the chemical composition of leachates obtained from leaching BOF slags with diluted HCl. The effect of adding NaOH and different amine-based organic solvents (PEI, MEA and AEEA) was investigated by considering an integrated process: CO2 -absorption and mineral carbonation. Ca conversion was below 15 wt.% in the absence of alkaline reagents as alkalinity is reduced when H2 CO3 is formed under permanent introduction of CO2 . The addition of a substantial amount of NaOH (20 g/L, Ca/Na ratio of 1:1) allowed to significantly increase the Ca-conversion yield, and the morphology of calcite particles was modified from scalenohedral-rhombohedral-type to rhombohedral shape by increasing the CO2 -gas flow rate from 0.008 to 0.5 L/min. During carbonation with the addition of amine-based organic solvents, MEA and AEEA showed the highest Ca-conversion, i.e. > 80 wt.%. A combination of vaterite and aragonite particles were produced at 30 °C, while the formation of pure aragonite prevailed when the temperature was increased up to 70 °C. The effect of Mg on the formation of aragonite particles was considered negligible due to the low initial concentration, although some traces of Mg were detected in the corresponding final PCC particles.